Twintuition - Double vision - Mowry, Tia; Mowry, Tamera (Harper, 2015)
"Cassie and Caitlyn Waters may be identical twins, but everything else about them is completely different. The only thing they can agree on is that neither of them is happy that have to move to middle-of nowhere Aura, Texas. Caitlyn tries to put a positive spin on getting a fresh start, but Cassie's busy plotting how to convince their mom they should move back to the big city as quickly as possible. But being the new kids isn't their only challenge. As the girls' birthday nears, they start experiencing strange visions...and what they see starts coming true! Caitlyn and Cassie first use this new sight for their own fun, but when they each see something serious, the twins must work together to change the future before it happens"...Jacket flap